Colon mucosal cells after combined radiotherapy and chemotherapy - Pleskovic, A; Zorc-Pleskovic, R; Vraspir-Porenta, O; Zorc, M; Petrovic, D (Folia biologica, 2001)
The aim of this study was to investigate early histological and stereological changes in enterocytes, lymphocytes, mast cells, serotonin- and somatostatin-secreting cells in colon mucosa the first day after the end of combined radiotherapy and chemotherapy. For experimental model 20 Beagle dogs were used. Ten dogs were given platinol every 5 days over 20 days and they were irradiated 20 days with 32 Gy (every second day with a fractional dose of 3.2 Gy) onto the whole pelvis and tail. Another 10 dogs represented a control group. For detection of apoptosis the TUNEL technique was used, whereas immunohistochemical methods were performed for detection of somatostatin- and serotonin-secreting cells, and for proliferating cell nuclear antigen in epithelial cells. The volume density of enterocytes in apoptosis was increased, and Vv of paracrine cells (mast cells, somatostatin and serotonin positive cells) was significantly increased in the treated group compared to the control group. In the treated group a significantly lower Vv of lymphocytes and PCNA-positive enterocytes was shown compared to the control group. The results of our experiments showed that combined radiotherapy and chemotherapy caused loss of enterocytes and lymphocytes early after the therapy. It was associated with an increased volume density of paracrine cells. These morphological changes in the colon mucosa might be the earliest changes leading to disruption of the mucosal barrier, malabsoption syndrome, stenosis, inflammation and other complications resulting from the radiotherapy and chemotherapy.
Keywords: psi; kombinovaná terapie; kolon; enterocyty; Dogs; Cell Nucleus; cisplatina; Serotonin; serotonin; Cisplatin; koncové značení zlomů DNA in situ; In Situ Nick-End Labeling; somatostatin; buněčné jádro; Colon; zvířata; proliferační antigen buněčného jádra; Immunohistochemistry; imunohistochemie; Somatostatin; apoptóza; Enterocytes; Animals; Combined Modality Therapy; Apoptosis; Proliferating Cell Nuclear Antigen